Polarization of THP-1-Derived Macrophage by Magnesium and MAGT1 Inhibition in Wound Healing - Oh, Mun Ho; Jang, JaeHyuk; Lee, Jong Hun (Archives of Plastic Surgery, 2023)
Background Macrophages play a major role in wound healing and prevent infection from the outside. Polarization conversion of macrophages regulates aspects of inflammation, and two macrophages, M1 (classically activated) and M2 (alternatively activated), exist at both ends of broad-spectrum macrophage polarization. Thus, we aimed to investigate whether macrophage polarization can be artificially regulated. To this end, MgSO4 and small-interfering RNA (siRNA) targeting magnesium transport 1 (MAGT1) were used to investigate the effects of intracellular magnesium (Mg2+) concentrations on the differentiation of macrophages in vitro.Methods THP-1 derived macrophages maintained in a culture medium containing 5 mM MgSO4 and siRNA to inhibit the expression of MAGT1. As comparative groups, THP-1 derived macrophages polarized into M1 and M2 macrophages by treatment with M1, M2 inducer cytokine. The polarization status of each group of cells was confirmed by cell surface antigen expression and cytokine secretion.Results We found that MgSO4 treatment increased CD163 and CD206, similar to the effect noted in the M2 group. The expression of CD80 and HLA-DR was increased in the group treated with MAGT1 siRNA, similar to the effect noted in the M1 group. Functional assays demonstrated that the group treated with MgSO4 secreted higher levels of IL-10, whereas the MAGT1 siRNA-treated group secreted higher levels of IL-6 cytokines. Additionally, the conditional medium of the Mg2+ treated group showed enhanced migration of keratinocytes and fibroblasts.Conclusion Mg2+ can help to end the delay in wound healing caused by persistent inflammation in the early stages.
Keywords: wound healing; magnesium; macrophage; differentiation; polarization